(untitled) (Research, Society and Development, 2021)
Objective: To characterize the impact of excessive exposure to blue light emitted by digital devices on the vision of teenagers and young adults. Methods: Integrative literature review carried out in the BVS, PubMed and Capes Journal databases. The searches covered the period 2016-2021, with complete and original articles involving selected groups of teenagers or young adults. Results: Six articles were selected, consisting of observational descriptive cross-sectional studies with a self-administered questionnaire, with an average of 403 members aged between 18 and 31 years old, most of them female. Only four studies established a correlation between prolonged use of digital devices and the manifestations of computer vision syndrome, with variations in screen use time. Conclusion: There is no consensus in the literature showing which period of exposure would be harmful for the appearance of ocular manifestations, requiring further studies considering the environmental and behavioral aspects of each individual.